Are Women Doing It For Themselves? Gender Segregation and the Gender Wage Gap - Nikolaos Theodoropoulos; John Forth; Alex Bryson (Institute of Labor Economics (IZA), 2019)
Using matched employer-employee data from the 2004 and 2011 Workplace Employment Relations Surveys (WERS) for Britain we find a raw gender wage gap (GWG) in hourly wages of around 0.18-0.21 log points. The regression-adjusted gap is around half that. However, the GWG declines substantially with the increasing share of female managers in the workplace. The gap closes because women's wages rise with the share female managers in the workplace while men's wages fall. Panel and instrumental variables estimates suggest the share of female managers in the workplace has a causal impact in reducing the GWG. The role of female managers in closing the GWG is more pronounced when employees are paid for performance, consistent with the proposition that women are more likely to be paid equitably when managers have discretion in the way they reward performance and those managers are women. These findings suggest a stronger presence of women in managerial positions can help tackle the GWG.
Keywords: J16; J31; M52; M54; 330; gender wage gap; female managers; performance pay